Surgical Options for Management of Malignant Pleural Mesothelioma in the Current Era - Loubani, Mahmoud; S. Qadri, Syed; Hussain, Azar; A. Chaudhry, Mubarak; A. Kastelik, Jack (Current Respiratory Medicine Reviews, 2016)
Malignant pleural mesothelioma is an asbestos-linked cancer associated with a very poor prognosis. Surgical interventions form an important aspect of the management of this aggressive form of cancer. However, debate continues regarding the different treatment options available. Video assisted thoracoscopic surgery (VATS) has been the procedure of choice for the diagnosis of malignant pleural mesothelioma as big samples can be taken from multiple areas of the chest under direct vision. It may also be used as a palliative procedure to drain pleural effusion and perform pleurodesis. Other surgical options include extrapleural pneumonectomy, radical pleurectomy or extended pleurectomy decortication and pleurectomy and decortication. Frequently, these surgical procedures are performed in conjunction with chemotherapy and/or radiotherapy. In this review we will discuss the developments and remaining controversies of surgery in the context of malignant pleural mesothelioma.
Keywords: Asbestos